Integrating the Enzymatic Syntheses of Lactulose, Epilactose and Galacto-Oligosaccharides - Arenas-Salinas, F; Vera-Vera, C (Institution of Chemical Engineers, 2024)
A mutant of cellobiose 2-epimerase from Caldicellulosiruptor saccharolyticus (CsCE H356N) was studied for obtaining higher yield of oligosaccharides than by lactose transgalactosylation with Aspergillus oryzae β-galactosidase (AO-βG). Firstly, heterologous production of CsCE H356N was optimized in Luria-Bertani broth and minimal medium. Then, CsCE H356N and AO-βG were used for the synthesis of oligosaccharides varying the sequence of reactions, temperature, and enzyme load. Reactions sequence did not affect the global yield (∼51 %) but modified the product composition. At the best conditions tested, the global yield increased twice with respect to GOS synthesis with AO-βG (25.6 %). When GOS synthesis was followed by the isomerization/epimerization of unreacted lactose, the final product had a higher content of lactulose and GOS than when the reactions sequence was inverted. In the former case lactulose-derived oligosaccharides (fGOS) and fructose were absent, while in the latter the final product mainly contained fGOS, small amounts of GOS, lactulose and fructose. Epilactose content was similar in both sequences. © 2024 Institution of Chemical Engineers (IChemE)